Multimodal Assessment and Characterization of Sicca Syndrome - Kramer, Emelie; Seeliger, Tabea; Skripuletz, Thomas; Gödecke, Vega; Beider, Sonja; Jablonka, Alexandra; Witte, Torsten; Ernst, Diana (Frontiers in Medicine, 2021)
Background: Sicca syndrome represents a heterogeneous group of conditions, such as Sjögren syndrome, causing xerophthalmiaand xerostomia. This study characterizes in depth patients with Sicca syndrome and evaluates salivary gland ultrasound (SGUS). Methods: Principal component analysis and hierarchical clustering of clinical parameters, such as ESSPRI, ESSDAI and laboratory data, were performed on all referrals for assessment of Sicca symptoms between October 2018 and March 2021. SGUS and labial gland biopsies were compared across groups. Results: A total of 583 patients were assessed. Objective dryness was confirmed in 73% of the patients. Cluster analysis identified 3 groups with post-hoc analysis confirming distinct phenotypes: Somatic Group (283/583; 49%) with more frequent symptoms but limited objective dryness; Dry Without Autoimmune Features (DAFneg, 206/584; 35%), and Dry With Autoimmune Features (DAFpos, 94/584;16%). DAFpos patients had highest autoantibody titers (anti-SSA(Ro) 240 vs. 3.6 vs. 3.8; p < 0.001), most extra-glandular manifestations (p < 0.001), and highest median SGUS Score (DAFpos: 8 [IQR 4–10] vs. SG: 2 [1–4] vs. DAFneg 4 [2–5]; p < 0.001). No tangible correlation with primary Sjögren syndrome criteria was observed. Discussion: SGUS score correlated with a subset of patients with Sjögren syndrome, identified in the DAFpos cluster. This study highlights heterogeneity within sicca and, indeed, Sjögren syndrome, highlighting the need for further studies.